English language learning through networked written interaction - Guerra, Luis (2013)
The advance of globalization and the information technology revolution call for fundamental changes in foreign language teaching and learning. However, according to Warschauer & Kern (2005:2) “the computer, like any other technological tool used in teaching (…) does not in and of itself bring about improvements in learning.” Instead, they propose that we should “look to particular practices of use in particular contexts” so that we might be able to ascertain if the use of network-based language teaching leads to better language learning. In other words, we should describe and evaluate the social context of a specific practice of use as far as the learners, their motivation, the setting and features of their social interaction and their use of language are concerned. This paper aims to address some pedagogical issues in the use of software applications in foreign language teaching. More specifically, it attempts to examine the results of an online written interaction activity among advanced (C2) students of English a foreign language at the University of Évora, Portugal, through Skype, a software application that allows users to communicate by voice calls and instant messaging over the internet. It also examines the potential benefits of synchronous conference as pointed out by Kern at al. (2008:282), namely: (1) encouragement of a collaborative spirit among students, and (2) enhanced motivation for language practice and, in particular, greater involvement of students who rarely participated in oral discussions. Moreover, it analyses some features of language use, the role of the teacher, and the fulfillment of instructional goals. In sum, this study hopes to briefly explore the relationship between the use of computer networks and language teaching.